Arthur Schnitzler : Der Witwer. Die Gefährtin Historisch-kritische Ausgabe - Rauchenbacher, Marina (De Gruyter, 2023)
The 14th volume of the "Historical-Critical Edition of Arthur Schnitzler's Early Works" - edited by Konstanze Fliedl since 2010 - presents Schnitzler's novella "Der Witwer" and the one-act play "Die Gefährtin," which Schnitzler developed from the novella. The entire corpus of material is genetically reconstructed; the manuscripts are reproduced as facsimiles and provided with diplomatic transcriptions. Furthermore, the volume includes reading texts with a critical apparatus, detailed descriptions of the genesis, premieres, and the printing history based on additional sources and testimonies, and a commentary.